Analysis of Women Leadership Behavior in the Personnel and Human Resources Development Agency (BKPSDM) of Southeast Minahasa Regency - Nova Yohana Kaligis; Grace. J. Soputan; Aditya Pandowo (International Journal of Applied Business and International Management, 2020)
This study aims to determine the women leadership behavior in the Personnel and Human Resources Development Agency (BKPSDM) of South East Minahasa Regency. This study made use a qualitative approach with descriptive methods and identified two key informants, the secretary and implementing staff of the BKPSDM. Data were collected by interviews and questionnaires. After rigorous examination, it was discovered that the most prominent leadership behavior is feminine leadership in which the leader is oriented more toward relations with subordinates through attitudes by frequently coordinating with various parties in making decisions, satisfying aspirations, being open to subordinates and guiding them when making mistakes at work. The leadership style combines several styles tailored to the situation at hand.